Enemy at the gates - Mills, Kyle, 1966-; Flynn, Vince, 1966-2013 (Flynn, Vince, 1966-2013. Mitch Rapp novel., 2021)
"Mitch Rapp has worked for a number of presidents over his career, but Anthony Cook is unlike any he's encountered before. Cunning and autocratic, he feels no loyalty to America's institutions and is distrustful of the influence Rapp and CIA director Irene Kennedy have in Washington. Meanwhile, when Kennedy discovers evidence of a mole scouring the Agency's database for sensitive information on Nicholas Ward, the worlds first trillionaire, she convinces Rapp to take a job protecting him. In doing so, he finds himself walking an impossible tightrope: Keep the man alive, but also use him as bait to uncover a traitor who has seemingly unlimited access to government secrets"--